2012
DOI: 10.1007/s10948-012-1795-7
|View full text |Cite
|
Sign up to set email alerts
|

Microwave Properties of Nb/PdNi/Nb Trilayers

Abstract: We combine wideband (1-20 GHz) Corbino Disk and Dielectric Resonator (8.2 GHz) techniques to study the microwave properties in Nb/PdNi/Nb trilayers, grown by UHV dc magnetron sputtering, composed by Nb layers of nominal thickness d (S) =15 nm, and a ferromagnetic PdNi layer of thicknesses d (F) =1, 2, 8 and 9 nm. We focus on the vortex state. Magnetic fields up to H (c2) were applied. The microwave resistivity at fixed H/H (c2) increases with d (F) , eventually exceeding the Bardeen-Stephen flux-flow value. Vo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 15 publications
1
7
0
Order By: Relevance
“…Below we present theoretical description consistent with available flux-flow resistivity data for SFS 17 and discuss low-field flux-flow resistivity experiment, where resisitivity of SFS is proportional to the vortex density in agreement with Bardeen-Stephen theory. We argue that in the π-state the relevant numeric proportionality coefficient exhibits universal h-independent behaviour providing a way to distinguish between the 0 and π state of SFS by single flux-flow resisitivity measurement.…”
Section: Superconductor-ferromagnet-superconductorsupporting
confidence: 61%
“…Below we present theoretical description consistent with available flux-flow resistivity data for SFS 17 and discuss low-field flux-flow resistivity experiment, where resisitivity of SFS is proportional to the vortex density in agreement with Bardeen-Stephen theory. We argue that in the π-state the relevant numeric proportionality coefficient exhibits universal h-independent behaviour providing a way to distinguish between the 0 and π state of SFS by single flux-flow resisitivity measurement.…”
Section: Superconductor-ferromagnet-superconductorsupporting
confidence: 61%
“…Thus, for (ω − ω F )/ω F ≪ 1 the thickness d may be of the order of or larger than the domain wall width. Finally, we will discuss briefly a recent paper by Torokhtii et al, 21 where the flux-flow resistivity in Nb/PdNi/Nb trilayers has been measured. It has been reported that in the presence of the magnetic PdNi layer the flux-flow resistivity in Nb exceeds the Bardeen-Stephen estimate, 33 as if the vortex viscosity is reduced by the interaction with magnetic moments.…”
Section: Magnon Excitation In Sfmentioning
confidence: 94%
“…Experimentally, the oscillating current in the superconductor can be created using the microwave technique (for example, see Ref. 21). Then, the surface impedance yields information about the high-frequency properties of the sample -see Sec.…”
Section: Magnon Radiation By a Harmonically Oscillating Vortex Lamentioning
confidence: 99%
“…However, additional phenomena arise in the flux-flow resistivity with increasing d F . In Figure 5(e) we report the plateau resistivity of the normalized curves ρ v1 (f )/ρ n , that is an experimental measure of ρ ff , as a function of d F and at the same reduced temperature T/T c ≃ 0.86 and reduced field H/H c2 ≃ 0.5 [45]. It is immediately seen that, when the effect of the fer-romagnetic layer becomes appreciable, the fluxflow resistivity increases and exceeds the Bardeen-Stephen value.…”
Section: Microwave Vortex Response In S/f/s Heterostructuresmentioning
confidence: 99%